Surgical correction of coarctation of the aorta featuring an incomplete circle of Willis. (3rd April 2020) - Sonobe, Aiko; Kato, Hideyuki; Mathis, Bryan J; Hiramatsu, Yuji
Abstract: Although devastating complications during simple coarctation of aorta repair now occur less frequently, some unique cases still require extra caution. Here, we report a case of coarctation of the aorta with a rare anomaly in the circle of Willis and an aberrant right subclavian artery, which required a thorough surgical strategy that prevented cerebral malperfusion.